The Implementation of Daily Five Literacy Framework in Improving English Literacy Skills for Primary Program - Murniasih, Tri Ery; Suwastini, Ni Komang Arie; Adnyani, Ni Luh Putu Sri (International Journal of Elementary Education, 2023)
The obstacles encountered in online learning are teacher shortages and technical difficulties, barriers, resources, social contacts, and difficulties in delivering subjects and managing time to engage with students and evaluate their work. This study explores teachers' perceptions of the influence of the Daily Five Literacy Framework on literacy programs in the classroom. This preliminary research is designed as qualitative research following the interactive qualitative data analysis model of Miles, Huberman, and Saldaña. The study included three teachers in three different grades of fourth grade, who were observed over five days as they implemented the five habits in the Daily Five Literacy Framework in their classrooms. The research results revealed that the three teachers consistently applied the five habits, with relatively low fluctuations. However, the implementation was generally less intensive on Day 3 for the three teachers because they had to complete and submit their teaching administration to the school every Wednesday, which happened to be the 3rd Day of implementation. As a preliminary study, these findings indicate the need for further implementation of the literacy framework to reveal teacher consistency, the effectiveness of the framework for building literacy habits, and to identify factors outside of instructional design that may negatively impact the successful implementation of the framework.